Developmental changes in independent bimanual coordination: evidence from the circles–lines coupling task in children aged 5–13 years - Nobusako, Satoshi; Hashizoe, Kenya; Nakai, Akio (Frontiers in Human Neuroscience, 2025)
IntroductionBimanual coordination, particularly the ability to perform independent and simultaneous asymmetric movements with both hands, is essential for many daily activities and develops throughout childhood. However, its developmental trajectory remains unclear. This study investigated age-related changes in bimanual coordination using the bimanual circles–lines coupling (BC) task and explored its relationship with fine motor skills in children aged 5 to 13 years.MethodsA total of 150 typically developing children completed the BC task under unimanual (UM) and bimanual (BM) conditions. The bimanual coupling effect (BCE), reflecting interference between concurrent motor programs, was calculated as the difference in ovalization index (OI) between the two conditions. Fine motor abilities were assessed using the manual dexterity component of the Movement Assessment Battery for Children–2nd Edition (M-ABC2), yielding scores for preferred hand, non-preferred hand, bimanual, and handwriting skills.ResultsAcross age groups, OI was significantly higher in the BM than in the UM condition, indicating the presence of BCE. Both UM-OI and BM-OI significantly decreased with age, while BCE showed a weak but significant negative correlation with age. These findings suggest a gradual developmental improvement in the ability to perform independent bimanual movements. Partial correlation analyses, controlling for age, revealed significant associations between BCE/BM-OI and bimanual motor skills, suggesting that the ability to overcome intermanual interference is closely linked to age-appropriate bimanual coordination.DiscussionGiven that asymmetric bimanual control involves not only the fronto-parietal network but also executive functions in the prefrontal cortex and interhemispheric motor communication, the present behavioral findings may reflect multifaceted neural maturation during childhood—specifically, the development of the fronto-parietal network, prefrontal cortex, and transcallosal motor pathways. The BC task, which requires only minimal equipment and administration time, may serve as a valid, cost-effective, and developmentally sensitive tool for quantifying bimanual coordination abilities in children. Its practical applicability highlights its potential as an assessment measure for motor development in both research and clinical contexts. This study contributes to a better understanding of how independent bimanual control emerges during childhood and may inform future approaches to evaluating fine motor function in pediatric neuromotor disorders.